REKONSTRUKSI RESTORATIVE JUSTICE SYSTEM DALAM TINDAK PIDANA PENGANIAYAAN BERBASIS KEADILAN HUKUM - Juyanto Juyanto (UNISSULA, 2016)
If occur a persecution the victim or usually a weak person will seek justice by report to the police or the parties that can find a way out to get justice or to report for a scare off in order to avoid persecution in the future. Police in this matter is investigator that receiving report of complaints obliged to do the step of investigation to investigation.Toward someone who has been set as a suspect by the fulfillment of evidence because committing an unlawful act usually want to finish their supposition including in the case of persecution by contacting the victim, the victim's family asking help to anyone deemed capable of including community leaders to mediate on the matter, even less so will ask the mediation of the Police investigators to resolve the issue because it was considered capable of including cases of persecution.The Police Investigator of West Kotawaringin Resort with space limitations of prisoners that held in the case of persecution based on police discretion in the belief capable of resolving and foster the suspect amicably, by way suspended imprisonment of the suspect then do coaching religiously by attending pilgrims I'tikaf from mosque to mosque for 40 ( forty ) days , although this case is not an offense act of complaints so that the case is still running to follow the law process although there is a peace agreement because the public prosecutor asked for the case to be trial in judicial process so that the reported cases are legally proceed to prosecution.